Peranan Teknologi dalam Mendukung Perekonomian di Desa Mojowatesrejo - Wyda Lusiana; Alvia Nur Jannah; Miftakhul Fitriyah; Rizka Lailiya Tasya; Robi’atul Adawiyah; Rosi Diah Bela; Meta Silvi Rosalia; Rafif Farrydika; Risky Nurus Sobah; Eko Setiyo Budiono; Juan Ariwangsa; Aditya Indra Wardana; Krisna Laksana Putra; Dhena Mustikawati; Orka Maya Armayudha; Ratna Dewi Rama Diningtias; Adam Wirasunu; Mochammad Nur Mahmudi; Tazkia Rizki Adillah; Hari Widiastuti; Indyka Giran Mahardani; Indah Lestiana; Aldo Putra Pratama (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Technology is a system used to market via social media in the current era of globalization. The socialization activity with the theme “The Role of Technology in Improving the Economy in Mojowatesrejo Village” was held on December 13, 2024 at the Mojowatesrejo Village hamlet hall. This socialization activity is carried out to teach the public about the role of digital technology, not only that, but also to carry out socialization and direct practice in using digital through social media. Business activities in Mojowatesrejo village include the agricultural, livestock and craft sectors. After learning about the important role of digital technology, people were very enthusiastic and began to actively use social media to promote their products.